The Use Of Continuous System Processor For Reducing Color AndTurbidity Content In The Peat Water - Hasbi, M.; ', Aris; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractPeat water is naturally brownish colored and it has high turbidity and thus it is not sufficient to support the life of fish, especially Cyprinus carpio. To understand the effectiveness of the continuous system processor to reduce the color and turbidity in the peat water and to understand the ability of C. carpio to live in the treated peat water, a study has been conducted in May 2014. The peat water was obtained from the Tarai River and then was processed using “a continuous processor”. The water was pumped into water tank (120L), added with lime (225 gr), Aluminum Sulphate (225 gr), aerated and filtered with layers of zeolit, charcoal and sand. Sampling was conducted 4 times, once/week. Results shown that after being treated, the color of the water become clear (from around 890 to 7.49 PtCo) and the effectiveness was 99.17%. The turbidity decrease, from 40.0 NTU into 2.61 NTU (effectiveness 93.41%). Survival rate of Cyprinus carpio that were reared in the treated water was 100%. Based on data obtained, it can be concluded that the continuous system is effective to reduce the color and turbidity of the peat water.Keywords : Peat Water, Continuous system processor, water color, turbididty, Cyprinus carpio.